Single-cell genomics identifies cell type-specific molecular changes in autism - Velmeshev, Dmitry; Schirmer, Lucas (Science, 2019)
Brain cell transcriptomes in autism - Autism manifests in many ways. Despite that diversity, the disorder seems to affect specific cellular pathways, including those observed in the neocortex of patients' brains. Velmeshev et al. analyzed the transcriptomes of single brain cells, including neurons and glia, from patients with autism. Single-nucleus RNA sequencing analysis suggested that affected pathways regulate synapse function as well as neural outgrowth and migration. Furthermore, in patient samples, specific sets of genes enriched in upper-layer projection neurons and microglia correlated with clinical severity. - Science, this issue p. 685 - Despite the clinical and genetic heterogeneity of autism, bulk gene expression studies show that changes in the neocortex of autism patients converge on common genes and pathways. However, direct assessment of specific cell types in the brain affected by autism has not been feasible until recently. We used single-nucleus RNA sequencing of cortical tissue from patients with autism to identify autism-associated transcriptomic changes in specific cell types. We found that synaptic signaling of upper-layer excitatory neurons and the molecular state of microglia are preferentially affected in autism. Moreover, our results show that dysregulation of specific groups of genes in cortico-cortical projection neurons correlates with clinical severity of autism. These findings suggest that molecular changes in upper-layer cortical circuits are linked to behavioral manifestations of autism. - Single-cell analysis categorizes brain cell types most affected by autism and correlates transcriptional alterations with clinical symptoms. - Single-cell analysis categorizes brain cell types most affected by autism and correlates transcriptional alterations with clinical symptoms.